Genetic Diversity and Selection Signatures Within Diannan Small-Ear Pigs Revealed by Next-Generation Sequencing - Fen Wu; Hao Sun; Shaoxiong Lu; Xiao Gou; Dawei Yan; Zhong Xu; Zhenyang Zhang; Qamar Raza Qadri; Zhe Zhang; Zhen Wang; Qiang Chen; Mingli Li; et al. (2020)
The research on genetic characterization of Chinese indigenous pig breeds is essential to promote scientific conservation and sustainable development of pigs. Here, we systematically surveyed the genomes of 75 unrelated Diannan small-ear (DSE) pigs that were from 3 diverse regions (Yingjiang County, Jinping County and Sipsongpanna in Yunnan Province) to describe their population structure, genetic diversity, inbreeding coefficient, and selection signatures. First, these individuals were sequenced and genotyped following the genotyping by genome reducing and sequencing (GGRS) protocol. A total of 438,038 autosomal SNPs were obtained and used for statistical analysis subsequently. The results showed that these DSE pigs were clearly differentiated into three separate clades revealed by the population structure and principal component analysis (PCA), which is consistent with their geographical origins. Both the results, effective population size (Ne) values and low heterozygosity shows that the DSE pigs had the low genetic diversity, which demonstrated the need of enhanced conservation strategies. Besides, we found the runs of homozygosity (ROH) with shorter segments (1-5 MB) predominated across the genome in DSE pigs and the inbreeding coefficients based on ROH (FROH) among subgroups were not significantly different. We also searched some candidate selection signatures within DSE pig population based on the ROH islands and iHS methods. Genes associated with meat quality (COL15A1, RPL3L and SLC9A3R2), body size (PALM2-AKAP2, NANS, TRAF7 and PACSIN1), adaptability (CLDN9 and E4F1), and appetite (TRM4) were identified as candidate targets. In conclusion, these findings can help to understand the genetic characterization and provide insights into investigating the molecular background of special phenotypes of DSE pigs to promote DSE pigs conservation and sustainability.